The suspension of mastery and the desire for imaginary : applying Jacques Lacan's theory of the imaginary to the beholder/image dialectic as realised in selected paintings by Lucy Cobern and Gerhard Richter - Cobern, Lucy Rebecca (Rhodes University, Faculty of Humanities, Department of Psychology)
This dissertation seeks to explore the nature of the self/other, subject/object dialectic that can be found in Jacques Lacan's theory of the Minor Stage and his notion of Imaginary mastery, and how this relationship can be re-read in terms of a beholder/image relationship. What I seek to demonstrate in exploring the relationship between the beholder and the image is the staging of two opposing emotions, aggression and desire and the consequential tussle for mastery that arises from the self/other, and hence the beholder/image, dichotomy. I seek to explore the reasons why such a beholder/image relationship becomes ambivalent, due to veiled, obscured and fragmented images.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Lacan, Jacques, 1901-1981 -- Criticism and interpretation; Richter, Gerhard, 1932- -- Criticism and interpretation